2013
DOI: 10.1159/000346546
|View full text |Cite
|
Sign up to set email alerts
|

Metallothioneins I/II Expression in Rat Strains with Genetically Different Susceptibility to Experimental Autoimmune Encephalomyelitis

Abstract: Objectives: Compared to the Dark Agouti (DA), the Albino Oxford (AO) rat strain exhibits lower susceptibility to the induction of experimental autoimmune encephalomyelitis (EAE). Here, we investigated the potential contribution of the heavy metal-binding proteins metallothioneins (MTs) I/II to these effects. Methods: Rats were immunized with bovine brain homogenate emulsified in complete Freund's adjuvant or only with complete Freund's adjuvant. The expression patterns of MTs mRNA and proteins and tissue conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 98 publications
1
6
0
Order By: Relevance
“…In our experiments the MT I/II expression correlated more with the peaks of clinical symptoms, in contrast to gp96, which was found in remission phases, suggesting that ER chaperones might be induced to ameliorate the accumulation of misfolded proteins in the CNS and protect neuronal cells against autoimmune attack. The importance of time-course evaluation of the data is emphasized also in the present study, which imply that EAE-resistant rats may more efficiently restrain the autoimmune response, owing to greater constitutive expression of hepatic MT I/II and IL-6 (Figures 1 and 3) and owing to an early upregulation of TGF- β in the liver [12]. …”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…In our experiments the MT I/II expression correlated more with the peaks of clinical symptoms, in contrast to gp96, which was found in remission phases, suggesting that ER chaperones might be induced to ameliorate the accumulation of misfolded proteins in the CNS and protect neuronal cells against autoimmune attack. The importance of time-course evaluation of the data is emphasized also in the present study, which imply that EAE-resistant rats may more efficiently restrain the autoimmune response, owing to greater constitutive expression of hepatic MT I/II and IL-6 (Figures 1 and 3) and owing to an early upregulation of TGF- β in the liver [12]. …”
Section: Discussionmentioning
confidence: 97%
“…Supporting the current knowledge about the prominent regulatory functions of metallothioneins in pathogenesis of EAE and other types of brain injuries [35, 45, 47], we previously reported that the expression metallothioneins I/II might be induced in both EAE-prone and EAE-resistant strain of rats, even in the presymptomatic phase of CR-EAE (on the seventh postimmunization day) in cells that form blood-brain and blood-cerebrospinal fluid barriers, in the cerebellar parenchyma and hippocampal dentate gyri, as well as in the liver of rats [12]. However, on the 12th postimmunization day, the levels of hepatic IL-6, TGF-beta, MTs, and gp96 were significantly greater in DA than in AO rats, implying that AO rats might better control the autoimmune reaction [12].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations